2011
DOI: 10.1038/bmt.2011.225
|View full text |Cite
|
Sign up to set email alerts
|

Intensification of GVHD prophylaxis with low-dose ATG-F before allogeneic PBSC transplantation from HLA-identical siblings in adult patients with hematological malignancies: results from a retrospective analysis

Abstract: Several studies have shown that chronic GVHD (cGVHD) is more frequent in patients receiving transplants from PBSC than in those receiving BM. In the setting of PBSC-unrelated transplants, the addition of anti-T-cell globulin (ATG) has shown a significant decrease in incidence/severity of cGVHD, without an increase in relapses or infections. However, no prospective data are yet available in the sibling setting. We retrospectively analyzed the effects of intensification of standard GVHD prophylaxis (CsA þ MTX) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 41 publications
5
15
0
1
Order By: Relevance
“…12 Now we investigated the impact of ATG-Fresenius on peripheral blood stem cell transplantation in HLA-identical siblings. Similar to the bone marrow experience, the difference in acute and chronic GVHD was significantly lower in those patients who received ATG 13 The reduction in GVHD by ATG seems to be dose dependent, 9 but prospective studies comparing different doses are lacking so far. More recently, Soiffer et al described a higher incidence of relapse after in vivo T-cell depletion and dosereduced conditioning; however, here, mainly thymoglobulin and alemtuzumab were used.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…12 Now we investigated the impact of ATG-Fresenius on peripheral blood stem cell transplantation in HLA-identical siblings. Similar to the bone marrow experience, the difference in acute and chronic GVHD was significantly lower in those patients who received ATG 13 The reduction in GVHD by ATG seems to be dose dependent, 9 but prospective studies comparing different doses are lacking so far. More recently, Soiffer et al described a higher incidence of relapse after in vivo T-cell depletion and dosereduced conditioning; however, here, mainly thymoglobulin and alemtuzumab were used.…”
Section: Discussionsupporting
confidence: 51%
“…[2][3][4][5][6] Although in unrelated stem cell transplantation the use of ATG within the conditioning regimen has been shown to reduce the risk of acute and chronic GVHD in retrospective as well as in prospective randomized trials [7][8][9][10] the role of ATG in HLA-identical sibling transplantation is less well defined, and smaller retrospective studies suggest similar benefit in reducing acute and chronic GVHD without an obvious increase in relapse as it has been observed in unrelated stem cell transplantation. [11][12][13] In a previous study from our own institution, we could show that ATG within the conditioning regimen in HLAidentical sibling transplantation in good-risk leukemia reduces the probability of acute and chronic GVHD without obvious risk of relapse. This study was based on 102 patients who were transplanted between 1999 and 2000 and received mainly bone marrow as stem cell source.…”
Section: Introductionmentioning
confidence: 99%
“…This effect had already been reported in previous studies. 5,7,9,10,22,23 Incidence of CMV and EBV reactivations, as well as symptomatic viral infections and bacterial BSI, but not invasive fungal infections were increased especially when using higher dose ATG. This can be attributed to the immunosuppressive effect of ATG.…”
Section: Discussionmentioning
confidence: 99%
“…7,10,12,13,23 It is possible that using lower doses for unrelated donor HSCT and related donor HSCT at higher risks of GvHD proves to be the best treatment option.…”
Section: Discussionmentioning
confidence: 99%
“…A number of phase II studies have assessed the impact of rabbit ATG in patients given unmodified grafts after myeloablative conditioning [46][47][48][49][50][51][52] (Table 2). Collectively, these studies suggested that ATG decreased the incidence of grade III-IV acute and chronic GVHD without increasing non-relapse mortality (some studies even found lower non-relapse mortality with ATG), increased the incidence of post-transplantation lymphoproliferative disorders, and improved quality of life.…”
Section: Non-randomized Studies Comparing Anti-thymocyte Globulin Vermentioning
confidence: 99%